Comparison of the Effect of Nifedipine Alone and the Combination of Nifedipine and Sildenafil in Delaying Preterm Labor: A Randomized Clinical Trial - Elham Mohammadi; Somayyeh Noei Teymoordash; Ali Reza Norouzi; Fatemeh Norouzi; Hamid Reza Norouzi (Tehran University of Medical Sciences, 2021)
Objective: Recently, sildenafil as a drug effective in relaxing smooth muscles can be used as an adjunct to delay the onset of uterine contractions and therefore the occurrence of preterm labor. The aim of this study was to evaluate the effect of nifedipine combination with sildenafil on preterm delivery compared with nifedipine alone. Materials and methods: This randomized double-blinded clinical trial was performed on pregnant women with a gestational age of 26-34 weeks with singleton pregnancy and symptoms of preterm delivery. The mothers were randomly assigned into two groups receiving nifedipine plus sildenafil or those receiving nifedipine alone. The time of delivery, maternal and neonatal complications were compared between the two groups. Results: Mothers who received the combination therapy experienced significantly lower preterm delivery within 72 hours of intervention compared to nifedipine alone (4.5% versus 27.3%, p = 0.002). The rate of delivery during the first 7 days after discharge was 7.6% and 31.8% in nifedipine plus sildenafil and nifedipine alone, respectively (P = 0.001). The prevalence of neonatal respiratory distress syndrome (RDS) as well as mean birth weight was higher in the nifedipine group alone. Treatment protocol with nifedipine and sildenafil compared with nifedipine alone was associated with a significant increase in preterm delivery delay (beta =-5.819, p = 0.001). Conclusion: The use of sildenafil in addition to nifedipine causes more delay in delivery in cases of preterm labor, followed by lower risk for RDS, reduces neonatal intensive care unit (NICU) admission, and preserves neonatal birth weight.